Defense Responses of Wheat Seedling under Biotic Stress Mimicked by the Linear β-(1,3)-Glucan (Global Journal of Science Frontier Research, 2020)
Reactive oxygen species (ROS) production causes damage, and to better deal with the toxic effects of ROS, the seeds have developed detoxification mechanisms, among which the enzymes of the antioxidant system (catalase, superoxide dismutase, ascorbate peroxidase ). Another result supports the link between ROS and redox regulation catalyzed by redoxin family in the seed. Among which, thioredoxins (Trxs) and peroxiredoxins (Prxs), particularly 1-Cys-Prx, expressed during maturation and germination steps.
Keywords: biotic stress; laminarin; peroxyredoxins; pr proteins; thioredxoin; wheat seedling